Characterization of a tannase from Emericela nidulans immobilized on ionic and covalent supports for propyl gallate synthesis - Gonçalves, Heloísa Bressan [UNESP]; Jorge, João Atílio; Pessela, Benevides Costa; Lorente, Glória Fernandez; Guisán, José Manuel; Guimarães, Luis Henrique Souza (Springer Nature, 2013)
The extracellular tannase from Emericela nidulans was immobilized on different ionic and covalent supports. The derivatives obtained using DEAE-Sepharose and Q-Sepharose were thermally stable from 60 to 75 °C, with a half life (t50) >24 h at 80 °C at pH 5. 0. The glyoxyl-agarose and amino-glyoxyl derivatives showed a thermal stability which was lower than that observed for ionic supports. However, when the stability to pH was considered, the derivatives obtained from covalent supports were more stable than those obtained from ionic supports. DEAE-Sepharose and Q-Sepharose derivatives as well as the free enzyme were stable in 30 and 50 % (v/v) 1-propanol. The CNBr-agarose derivative catalyzed complete tannic acid hydrolysis, whereas the Q-Sepharose derivative catalyzed the transesterification reaction to produce propyl gallate (88 % recovery), which is an important antioxidant. © 2012 Springer Science+Business Media Dordrecht.
Keywords: Emericela; Enzyme immobilization; Propyl gallate; Tannase; Tannin acyl hydrolase; 1-propanol; Extracellular; Free enzyme; Half lives; Q-Sepharose; Tannic acid; Thermally stable; Transesterification reaction; Catalysis; Flavonoids; Thermodynamic stability; Synthesis (chemical); carboxylesterase; gallic acid propyl ester; immobilized enzyme; tannase; tannin derivative; chemistry; Emericella; enzyme stability; enzymology; metabolism; pH; temperature; Carboxylic Ester Hydrolases; Enzyme Stability; Enzymes, Immobilized; Hydrogen-Ion Concentration; Propyl Gallate; Tannins; Temperature